Does perioperative allogeneic blood transfusion worsen the prognosis of patients with hepatocellular carcinoma? A meta-analysis of propensity score-matched studies - Hu, Lingbo; Li, Zhenyu; Qiao, Yingli; Wang, Aidong (Frontiers in Oncology, 2023)
Background Allogeneic blood transfusion is required in a part of liver resection. The effect of allogeneic blood transfusion on the prognosis of patients with hepatocellular carcinoma (HCC) remains controversial. To investigate whether perioperative allogeneic blood transfusion (PBT) affects the long-term prognosis of patients with HCC, we conducted a meta-analysis that included only propensity score-matched (PSM) studies. Methods The Cochrane Library, Embase, PubMed, and Web of Science databases were systematically searched to identify PSM studies that compared the long-term outcomes of allogeneic blood transfusion in resected HCC patients. Overall survival (OS) and recurrence-free survival (RFS) rates were calculated. Results This meta-analysis included 9 PSM studies with 12 datasets involving 2476 patients. Lower OS and RFS in HCC patients receiving allogeneic blood transfusion were observed than those in patients not receiving blood transfusion (OS: hazard ratio [HR], 1.34; 95% confidence interval [CI], 1.10–1.64; p < 0.01; RFS: HR, 1.29; 95% CI, 1.07–1.56; p < 0.01). Subgroup analysis revealed that among patients with BCLC A HCC, those receiving allogeneic blood transfusion had lower OS and RFS (OS: HR, 2.27; 95% CI, 1.61–3.21; RFS: HR, 2.11; 95% CI, 1.30–3.41). OS and RFS were similar in both groups of patients with BCLC B and C HCC. Conclusion The receipt of perioperative allogeneic blood transfusion is associated with a decrease in OS and RFS. These results seem to be reliable for patients in BCLC stage A. But more high-quality research is needed to confirm this conclusion.